Thirty years of the Chair of animal Physiology and Ethology at the University of Maribor - Devetak, Dušan (Acta entomologica slovenica (Ljubljana), 2022)
A brief review is given of the history of the Chair of animal Physiology and ethology at the University of Maribor, which celebrates 30 years of teaching and research in 2022. the focus of the research group has been the integration of the structure and function of insect sensory organs, insect vision, and biophysical, ethological and ecophysiological aspects of prey capture in predatory insects.
Keywords: antlions; Chrysoperla; Euroleon nostras; fiziologija čutil; insects; Neuroptera; plenilsko vedenje; predatory behaviour; sensory physiology; subgenual organ; subgenualni organ; substrate vibration; Univerza v Mariboru, Katedra za fiziologijo živali in etologijo; vibracije podlage; volkci; Žuželke